REDESAIN PEGANGAN TABUNG SINAR-X YANG ERGONOMIS DI RADIOLOGI RSUP SANGLAH MENURUNKAN KELUHAN MUSKULOSKELETAL, MENGURANGI KELELAHAN UMUM DAN MENINGKATKAN KECEPATAN PEMERIKSAAN - Susanta, I Putu Adi; Purnawati, Susy; Adiatmika, I Putu Gede (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic), 2017)
Radiology Installation is a unit of medical support services in a health facility that has a function as a means of patient diagnosis. In RSUP Sanglah there are 5 units of radiology sub-section such as Central Radiology, IRD, Wing Amerta, Central Surgery Room and Cath Lab Room which all have a goal of providing quality diagnostic value to patients and society. Problems occurring within the radiology unit are the incidence of work-related musculoskeletal complaints, increased general fatigue in workers, as well as decreased speed of examination by radiographers in service. This can be caused by a mismatch between the work tool and its users. Research has been conducted with intervention of redesign of X-ray tube handling through user anthropometry aims to know how big the effect of X-ray tube grip design improvement to musculoskeletal complaints, general fatigue and increased examination speed by radiographer. The subject anthropometry data is used as the basis for redesigning the X-ray tube handle. The design of the study using Treatment By Subject Designs with a large sample of 12 people who became the control group as well as the intervention group. Subjects were subjected to redesigned X-ray tube handles or grips that have been improved in shape and design more ergonomically adapted to the anthropometry of the subject body. Musculoskeletal complaints were assessed with Nordic Body Map questionnaires from NIOSH Japan, generalized fatigue disorder with 30 general fatigue items, and the examination speed by radiographers was obtained by measuring the time of the radiologic treatment on the number of checks performed. Shapiro - Wilk test was performed to determine the normality of data at significance level (? = 0,05). Differential comparative test between pre-repair and post-design improvement of musculoskeletal complaints, general fatigue and speed of examination using paired t-test at significance level ? = 0.05 It was found that in the intervention group the use of redesigned X-ray tubes could significantly decrease musculoskeletal complaints (p <0.05) by 10.42%, significantly reducing general fatigue by 22.38% (p <0.05 ) and increased the examination rate by 12.50% (p <0.05). Thus it can be concluded that the improved X-ray tube handle design can decrease musculoskeletal complaints, reduce general fatigue and increase the speed of inspection by radiographers at Sanglah Hospital Denpasar.